2005
DOI: 10.1097/01.inf.0000157095.75081.43
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Human Immunodeficiency Virus-Infected Children Receiving Highly Active Antiretroviral Therapy

Abstract: HAART improved the average weight gain of HIV-infected children from subnormal to normal after 1 year and improved average height growth to nearly normal after 2 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
71
2
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 19 publications
9
71
2
5
Order By: Relevance
“…16 On the other hand, after the antiretroviral drugs started to be used, the weight usually improves during the first year, and the height usually improves after the second year. 17 The high prevalence of dyslipidemia (88.3%) found in the present study is above the rate found in the literature. 8,18,19 This may have been caused by the fact that the references used for the analysis of serum lipids had a higher cutoff point.…”
Section: Discussionsupporting
confidence: 73%
“…16 On the other hand, after the antiretroviral drugs started to be used, the weight usually improves during the first year, and the height usually improves after the second year. 17 The high prevalence of dyslipidemia (88.3%) found in the present study is above the rate found in the literature. 8,18,19 This may have been caused by the fact that the references used for the analysis of serum lipids had a higher cutoff point.…”
Section: Discussionsupporting
confidence: 73%
“…[4][5][6] Many studies from developed countries using protease inhibitor (PI)-based ART regimen showed an improvement in growth of HIV-infected children after initiating ART. [7][8][9] Studies from Kenya and Uganda also showed significant improvements in weight and height as well as immunological and virologic parameters of perinatally HIVinfected children after ART initiation. 10,11 We had reported on the efficacy of ART in children participating in Thailand's national access to antiretroviral program.…”
mentioning
confidence: 99%
“…Baseline growth parameters in our cohort were worse than reported from the United States [28,29] and Spain [30] but similar to those reported from Thailand [10] and India [31]. Aurbipol et al report higher entry WAZ and HAZ, use of nevirapine-based regimen rather than efavirenz, and larger CD4% gains to week 48 as predictors of growth reversal after initiating ARV [32].…”
Section: Discussionmentioning
confidence: 35%
“…Nachman et al [28] reported a faster weight gain in children with higher baseline viral load counts. Baseline growth parameters in our cohort were worse than reported from the United States [28,29] and Spain [30] but similar to those reported from Thailand [10] and India [31].…”
Section: Discussionmentioning
confidence: 99%